THE INFLUENCE OF SKEPTICISM, AUDITOR EXPERIENCE, AND PROFESSIONAL ETHICS ON FRAUD DETECTION - Kinanti, Niken Ayu Eka; Novita, Novita (Jurnal Aplikasi Akuntansi, 2025)
This study examines the effect of skepticism, auditor experience, and professional ethics on fraud detection. The variables used are skepticism, auditor experience, and professional ethics as independent variables, and fraud detection as the dependent variable. This study uses primary data from a questionnaire submitted by distributing questionnaire links to auditors. The sample was 112 auditors who worked at the Public Accounting Firm in South Jakarta—data processing and analysis methods using Partial Least Squares (PLS). The results of this study indicate that skepticism and professional ethics have a positive and significant effect on fraud detection, while auditor experience does not affect fraud detection. This shows that auditors who have skepticism and apply professional ethics when carrying out their duties can detect fraud. This research implies that increasing auditor skepticism, experience, and ethics needs to be a focus in recruitment, training, and higher education curriculum to increase the effectiveness of fraud detection.